PENINGKATAN HASIL BELAJAR MATERI MENGHARGAI PENINGGALAN SEJARAH MENGGUNAKAN STRATEGI KWL SISWA KELAS IV MI AL – YASRIYAH - Ainah, Nor (FIKRUNA Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2022)
This study entitled: "Improving Learning Outcomes in Appreciating Historical Heritage Using the KWL Strategy for Grade IV MI AL - Yasriyah Students". The purpose of this research is to improve the learning outcomes of Appreciating Historical Heritage Using the KWL Strategy for Class IV MI AL - Yasriyah students. The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and reflection. Based on the results of action research that the KWL Strategy (Know, Want to know, Learner) can Improve Learning Outcomes in Appreciating Historical Heritage Materials for Class IV MI AL - Yasriyah students. Furthermore, the researcher recommends: (1) Teachers who have the same difficulties can apply the KWL (Know, Want to know, Learner) strategy to improve learning outcomes. (2) In order to get maximum results, it is hoped that teachers will make more interesting and varied KWL (Know, Want to know, Learner) strategies.